2021
DOI: 10.1101/2021.11.19.469321
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The proton motive force determinesEscherichia coli’s robustness to extracellular pH

Abstract: Maintaining intracellular homeostases is a hallmark of life, and key physiological variables, such as cytoplasmic pH, osmotic pressure, and proton motive force (PMF), are typically interdependent. Developing a mathematical model focused on these links, we predict that Escherichia coli uses proton-ion antiporters to generate an out-of-equilibrium plasma membrane potential and so maintain the PMF at the constant levels observed. The strength of the PMF consequently determines the range of extracellular pH over w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 84 publications
0
8
0
Order By: Relevance
“…Some studies highlighted the function of mitochondria in biosynthesis (Visser et al 1994 ) and lipid metabolism (Reiner et al 2006 ) and suggested that maintaining functional mitochondria in anaerobic conditions is an energy-costly process (Drgoň et al 1991 , Visser et al 1994 ). Moreover, recent reports allow us to speculate that maintenance of proton-motive force across cell membranes could be one of the factors leading to extra costs in anaerobic growth ((Malina et al 2021 , Terradot et al 2021 ), T. Pilizota, personal communication). Aerobically, the proton-motive force is generated by the electron transport chain in the mitochondrial inner membrane, and some of it is used for, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies highlighted the function of mitochondria in biosynthesis (Visser et al 1994 ) and lipid metabolism (Reiner et al 2006 ) and suggested that maintaining functional mitochondria in anaerobic conditions is an energy-costly process (Drgoň et al 1991 , Visser et al 1994 ). Moreover, recent reports allow us to speculate that maintenance of proton-motive force across cell membranes could be one of the factors leading to extra costs in anaerobic growth ((Malina et al 2021 , Terradot et al 2021 ), T. Pilizota, personal communication). Aerobically, the proton-motive force is generated by the electron transport chain in the mitochondrial inner membrane, and some of it is used for, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies highlighted the function of mitochondria in biosynthesis (Visser et al, 1994) and lipid metabolism (Reiner et al, 2006) and suggested that maintaining functional mitochondria in anaerobic conditions is an energy-costly process (Drgoň et al, 1991;Visser et al, 1994). Moreover, recent reports allow us to speculate that maintenance of proton-motive force across cell membranes could be one of the factors leading to extra costs in anaerobic growth ( (Malina et al, 2021;Terradot et al, 2021), T. Pilizota, personal communication). Aerobically, the proton-motive force is generated by the electron transport chain in the mitochondrial inner membrane, and some of it is used for, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…give rise to new generation of antibiotic-tolerant persister cells [4]. Efflux pumps, which cause multidrug resistance, need PMF to energize its pumping of antibiotics from cells [4][5][6].…”
Section: Introductionmentioning
confidence: 99%